The Native-Migrant Gap in the Progression into and through Upper-Secondary Education - Stefan C. Wolter; Maria Zumbühl (Institute of Labor Economics (IZA), 2017)
In this paper we follow the students that took the PISA 2012 test in Switzerland and analyze their transition into and progress in uppersecondary education. We observe a substantive difference in the rate of progress between natives and students with a migration background. One year after leaving compulsory school, the gap between the natives and migrants that are on-track – entering the second year of uppersecondary education – is 15 percentage points. Observable differences in cognitive and non-cognitive skills can explain the gap in the success rate within upper-secondary education, but cannot fully explain the difference in the transition rate into upper-secondary education. More refined analyses present results that are consistent with the hypotheses of differences in tastes, aspirations and incomplete or inaccurate information about the education system explaining the gap in the transition into post-compulsory education.
Keywords: I24; J15; J24; J62; J71; 330; education; migration; occupational choice